Cost effective utility‐solar photovoltaic based hybrid scheme for institutional buildings: a case study. Issue 5 (18th January 2017) - Parida, Adikanda; Chatterjee, Debashis
Abstract : Energy crisis and energy cost are always embedded with the educational institutions which significantly influences the scope for the sustainable growth of the organisation. Moreover, the increasing gap between energy demand and energy supply has become a global issue. The electrical power generation from the solar photovoltaic (PV) is the area of interest of many researchers in the recent past. However, the cost of energy is always a constraint for distributed renewable generation from solar PV. Based on the addressed issues, this study proposes a hybrid scheme consists of utility and solar PV for institutional buildings in a cost‐effective manner. This study identifies the scope for appropriate augmentation of solar PV with the existing power utility for minimum overall energy cost. Moreover, the proposed scheme is environmental friendly and can be extended to other utility based load centres with similar type of power demand characteristics.